(untitled) (Revista Sistemas de Producción Agroecológicos, 2014)
This research was conducted in Pacho, Cundinamarca, Colombia, where cows of the creole breed Blanco Orejinegro were evaluated with the help of a metric tape and zoometric gad. These measures permitted the elaboration of a correlation matrix defining that these animals correspond to a harmonic model. This way, we characterized the morphometrics characteristics of the BON breed. According to the correlation analysis, this study or the present work found that in the 88, 23% of de cases exist a positive correlation between the variables. Therefore, it is defined that these animals of the BON breed have a high degree of harmonicity in their morphostructural model.